Molecular Recognition and Visual Detection of G‐Quadruplexes by a Dicarbocyanine Dye. Issue 39 (11th August 2015) - Karg, Beatrice; Funke, Andrea; Ficht, Anna; Sievers‐Engler, Adrian; Lämmerhofer, Michael; Weisz, Klaus
Abstract The interactions of a dicarbocyanine dye 3, 3′‐diethylthiadicarbocyanine, DiSC2(5), with DNA G‐quadruplexes were studied by means of a combination of various spectroscopic techniques. Aggregation of excess dye as a result of its positive charge is promoted by the presence of the polyanionic quadruplex structure. Specific high‐affinity binding to the parallel quadruplex of the MYC promoter sequence involves stacking of DiSC2(5) on the external G‐tetrads; the 5′‐terminal tetrad is the favored binding site. Significant energy transfer between DNA and the dye in the UV spectral region is observed upon DiSC2(5) binding. The transfer efficiency strongly depends on the DNA secondary structure as well as on the G‐quadruplex topology. These photophysical features enable the selective detection of DNA quadruplexes through sensitized DiSC2(5) fluorescence in the visible region.